Determinants of market participation and marketing channels in smallholder groundnut farming: A case of Mudzi district, Zimbabwe. Issue 3 (16th April 2018) - Mango, Nelson; Makate, Clifton; Francesconi, Nicola; Jager, Matthias; Lundy, Mark
Abstract : This paper investigates the factors that are associated with market participation and choice of marketing channels by smallholder groundnut farmers in a semi-arid district of Zimbabwe. It contributes to the existing body of knowledge on groundnuts, especially the marketing aspect. Data was derived from a literature review and a cross-sectional household baseline survey. We applied simple logistic regression framework to determine the factors associated with market participation and choice of marketing channel. Our study findings show that land size, access to transport information, distance to the nearest town, age and education of the household head are among the important factors influencing the decision to participate or not to participate in selling of groundnuts. Choice of a particular marketing channel is influenced by distance to the nearest town, education level of the farmer, access to remittances, and market information. In conclusion. these findings suggest that an adjustment in each of these significant variables can influence the probability of market participation and an informed choice of marketing channels. In terms of policy, this implies that technological changes, infrastructural improvements, agricultural institutional developments, and capacity building of smallholder farmers can help to improve farmers' market participation and informed market channel choice.